Developing an App to Screen for Dual Disorders: A Tool for Improving Treatment Services in Mexico - Marín-Navarrete, Rodrigo; Torrens, Marta; Toledo-Fernández, Aldebarán; Mestre-Pinto, Joan Ignasi; Sánchez-Domínguez, Ricardo; Pérez-Lopez, Alejandro; Saracco-Alvarez, Ricardo; Madrigal-De León, Eduardo Ángel; Szerman, Nestor (Frontiers in Psychiatry, 2021)
Background: Previous studies in Mexico undertaken at residential facilities for treating substance use disorders (SUDs) reported that the prevalence of Dual Disorders (DDs) is over 65%. DDs pose a major challenge for the Mexican health system, particularly for community-based residential care facilities for SUDs, due to the shortage of certified professionals to diagnose and treat these patients. Moreover, the lack of standardized algorithms for screening for and evaluating DDs to refer patients to specialized services (whether private or public) hinders timely care, delaying the start of integrated treatment. The use of new technologies provides a strategic opportunity for the timely detection of DDs through the development of standardized digital applications for the timely detection of DDs. Objective: To develop an app to screen for DDs, which will contribute to referral to specialized services in keeping with the level of severity of psychiatric and addictive symptomatology, and be suitable for use by community-based residential care facilities for SUDs. Method: The research project was implemented in two stages. Stage 1 involved obtaining the psychometric properties of the Dual Diagnosis Screening Interview (DDSI). Stage 2 consisted of two steps to test the Beta version of the app and the quality of version 1.0. Results: The DDS obtained sensitivity and specificity scores above 85%. The app and its algorithm to screen for and refer DDs proved to be efficient and easy to apply with satisfactory community acceptance. Conclusion: The app promises to be a useful screening tool at residential addiction treatment centers.